Citizens who commit homicides - Willie, Warren S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article deals with a psychiatric study of 100 persons who have committed the crime of homicide. The subjects included in this study were examined during the time they were serving sentences in the prison system of the State of Michigan. The cases described here represent the first report on a series of approximately 2,000 persons who have committed the crime of murder.